Technology and managerial gaps in contract farming: The case of specialty crop production - Mishra, Ashok K.; Mayorga, Joaquin; Kumar, Anjani (Western Agricultural Economics Association, 2022)
We use a stochastic frontier approach corrected for self-selection to separate technology and managerial gaps between the treatment and control groups of smallholders in baby corn production in India. We also assess the impact of contract farming on output prices, profitability, and resource usage. We find that technical efficiency is consistently higher among contract farmers than among independent farmers and that significant technology and managerial gaps exist between contracted and independent growers. Ultimately, contract farming intervention benefits the livelihood of smallholders, increases efficiency, and reduces environmental degradation without compromising yield.